2002
DOI: 10.1016/s0735-1097(01)01768-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of heparin administration on the ischemic threshold of patients with coronary artery disease

Abstract: In patients with CAD, heparin reduces the ischemic threshold. Trimetazidine reduces the effects of heparin, probably by inhibiting FFA oxidation and enhancing glucose metabolism. The concomitant novel observation of reduced ET-1 release is likely to be also dependent on TMZ-induced improvement of endothelial metabolism or reduction of myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…GIK therapy for acute myocardial infarction was proposed in the 1960s, and several recent trials have shown promise in improving survival (19,21,46). There have also been several studies demonstrating the utility of the fatty acid oxidation inhibitors such as ranolazine and trimetazidine as antiischemic agents (23,52). One of the most commonly proposed mechanisms for the beneficial effects of increasing glucose oxidation at the expense of fatty acid oxidation is that this improves the coupling between glycolysis and glucose oxidation leading to lower accumulation of cellular protons and hence less intracellular acidosis (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GIK therapy for acute myocardial infarction was proposed in the 1960s, and several recent trials have shown promise in improving survival (19,21,46). There have also been several studies demonstrating the utility of the fatty acid oxidation inhibitors such as ranolazine and trimetazidine as antiischemic agents (23,52). One of the most commonly proposed mechanisms for the beneficial effects of increasing glucose oxidation at the expense of fatty acid oxidation is that this improves the coupling between glycolysis and glucose oxidation leading to lower accumulation of cellular protons and hence less intracellular acidosis (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, drugs such as ranolazine and trimetazidine, which shift the balance from fatty acids to carbohydrate use, appear to be beneficial in the setting of myocardial ischemia (23,52). There has also been renewed interest in the beneficial effects of glucose-insulin-potassium (GIK) infusions in the setting of acute myocardial infarction (19,21,46).…”
mentioning
confidence: 99%
“…It is well known that increased ET-1 levels are present in insulinresistant subjects, in Type 2 diabetic hyperlipidemic patients, and in atherosclerosis and cardiovascular disease (16,20,32). Moreover, in patients with coronary artery disease, a marked increase of ET-1 release was observed during exercise, in the presence of increased FFA levels (11).…”
Section: Effects Of Type 2 Diabetes Mellitus On Myocardial Insulin Rementioning
confidence: 95%
“…6 This has been the focus of many studies, leading to the development of putative fatty acid oxidation inhibitors such as trimetazidine and ranolazine for the treatment of ischemic disease. 7,8 Their protective effects are typically attributed to increased glucose oxidation and decreased fatty acid oxidation. 6 -8 Despite the continuing interest in GIK therapy and the apparent efficacy of trimetazidine and ranolazine, there is no consensus about the mechanisms underlying their beneficial effects.…”
mentioning
confidence: 99%